Toxicity of Cry2 proteins from Bacillus thuringiensis subsp. thuringiensis strain T01-328 against Aedes aegypti (Diptera: Culicidae) - Ricoldi, Marina Cabral [UNESP]; Figueiredo, Camila Soares [UNESP]; Desidério, Janete Apparecida [UNESP] (Instituto Biológico, 2018)
Bacillus thuringiensis subsp. israelensis has been used to control the Aedes aegypti (Diptera: Culicidae) mosquito larvae, the vector of virus diseases such as dengue, Chikungunya and Zika fever, which have become a major public health problem in Brazil and other tropical countries since the climate favors the proliferation and development of the transmitting vector. Because B. thuringiensis has shown potential for controlling insects of the Diptera order, this work aimed at testing the Bacillus thuringiensis subsp. thuringiensis strain T01-328 and its proteins Cry2Aa and Cry2Ab for control A. aegypti and at comparing the results to the B. thuringiensis subsp. israelensis specific dipteran strain. To this end, bioassays using spore-crystal of both strains, and Cry2Aa and Cry2Ab proteins from the heterologous expression in Escherichia coli, were performed against A. aegypti larvae. The results showed that the B. thuringiensis thuringiensis T01-328 has insecticidal activity against the larvae, but it is less toxic than B. thuringiensis subsp. israelensis. Cry2Aa and Cry2Ab proteins expressed heterologously were effective for controlling A. aegypti larvae. Therefore, the results indicate that the Cry2Aa and Cry2Ab proteins of the B. thuringiensis thuringiensis T01-328 can be used as an alternative to assist in the control of A. aegypti.

Bacillus thuringiensis subsp. israelensis vem sendo empregada no controle do díptero Aedes aegypti, vetor do vírus causador de doenças como dengue, febre Chikungunya e Zika, que se tornou um dos grandes problemas de saúde pública no Brasil e em outros países de clima tropical, que favorece a proliferação e o desenvolvimento do transmissor. Em virtude do potencial de B. thuringiensis no controle de dípteros, a proposta deste trabalho foi testar as proteínas Cry2Aa e Cry2Ab da linhagem de Bacillus thuringiensis subsp. thuringiensis T01-328 no controle de A. aegypti, em comparação à linhagem díptero específica B. thuringiensis subsp. israelensis. Para tanto, foram realizados bioensaios com larvas de A. aegypti com o esporo-cristal de ambas as linhagens, bem como com as proteínas Cry2Aa e Cry2Ab com expressão heteróloga em Escherichia coli. A linhagem B. thuringiensis thuringiensis T01-328 apresentou atividade inseticida contra as larvas, porém foi menos tóxica que a B. thuringiensis subsp. israelensis. As proteínas Cry2Aa e Cry2Ab expressas de forma heteróloga foram eficazes no controle de A. aegypti. Os resultados obtidos sugerem as proteínas Cry2Aa e Cry2Ab da linhagem B. thuringiensis thuringiensis T01-328 como alternativas para contribuir no controle do A. aegypti.
Toxicidade das proteínas Cry2 do Bacillus thuringiensis subsp. thuringiensis T01-328 contra Aedes aegypti (Diptera: Culicidae)
Keywords: Cry proteins; biological control; dengue; Zika; mosquito; proteínas Cry; controle biológico; dengue; Zika; mosquito